(ε,δ)-approximate Top-k query processing algorithm in wireless sensor networks - BI Ran; LI Jian-zhong; CHENG Si-yao (Tongxin xuebao)
A sampling based approximate Top-k algorithm was proposed that is adaptive for any data distribution.δ≥0 and 0≤δ<1 are respectively relative error bound and failure probability bound.The theoretical analysis demonstrates that for any δ≥0 and 0≤δ<1 the probability that the relative error bound of the results returned by this algorithm is larger than ε/（1+ε） is less than δ.So the proposed algorithm can reach arbitrary precision.Furthermore,an optimal sampling algorithm was proposed that supported the approximate Top-k query,and through the technique of data filtering the en-ergy consumption of communication was reduced.Theoretical analysis and simulation show that the proposed algorithm is efficient and consumes little energy.